SCIENTIFIC WRITING ON GERIATRIC NURSING MANAGEMENT WITH SERVICE EXCELLENCE FOR MRS. Z WITH HYPERTENSION AT THE ELDERLY SOCIAL SERVICE UNIT IN BINJAI, NORTH SUMATRA PROVINCE YEAR 2025 - Susiana Hutasoit; Erika; Ali Imran Sirait; Pegi Astri; Metodius Gulo; Mhd Ramadhan Nasri; Annisa Fitri (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Hypertension is one of the most common non-communicable diseases among the elderly and a leading cause of increased morbidity and mortality. In the context of gerontic nursing care, nurses play a crucial role in providing comprehensive and continuous care to improve the quality of life of older adults. This study aims to describe gerontic nursing care that prioritizes the principles of service excellence in managing hypertension in Mrs. Z, an elderly resident at the UPTD Elderly Social Service Binjai. The method used was a descriptive case study involving assessment, diagnosis, intervention, implementation, and evaluation stages. The results showed that non-pharmacological interventions, such as deep breathing relaxation techniques and hypertension exercises, effectively reduced pain complaints, improved physical activity, and enhanced Mrs. Z’s quality of life. The application of service excellence principles—professionalism, accountability, collaboration, empathy, and reliability—also strengthened the quality of nursing services provided. In conclusion, gerontic nursing care management based on service excellence is effective in addressing hypertension in the elderly and aligns with the achievement of SDGs points 3 and 4